A flexible framework of line power flow estimation for high-order contingency analysis. (September 2015) - Chen, Guo; Dai, YuanYu; Xu, Zhao; Dong, ZhaoYang; Xue, YuSheng
Highlights: We propose a flexible framework for high-order contingency analysis. A two-stage scheme is formed to make a compromise between accuracy and efficiency. The framework can provide significantly enhanced accuracy and satisfied efficiency. Abstract: Traditionally, power system contingency analysis involves massive power flow calculations, which are usually based on linear approximation methods, such as dc load flow model or distribution factors based method, for fast speed but with compromised accuracy. Particularly, the accuracy of power flow results can deteriorate with the increase of k given N – k contingency analysis. Consequently, the obtained results may provide misleading information by under estimating the impact of some severe contingencies. In order to effectively implement online N – k contingency analysis, we propose a flexible framework of power flow estimation, where generalized line outage distribution factors ( GLODF s) and ac power flow model are integrated together to formulate a two-stage scheme. At first stage, the Monte Carlo sampling technique is used to generate tables of computing errors for the hybrid ac -( GLODF s/ ac ) method. The achieved error information can then provide useful references in the second stage to select either ac - GLODF s based method or ac power flow model for N – k contingency analysis. Theoretically, the framework can provide significantly enhanced accuracy as well as satisfied efficiency. Finally, comprehensive case studies with the IEEE -118 bus system are given to validate the proposed framework.